In-vitro comparison of sealing ability of gutta-percha and AH26 sealer with cold ceramic through bacterial leakage and electrochemical method - Fatemeh Mokhtari; Jalil Modaresi; Henghameh Zandi; Iman Ramezanian Nik (Tehran University of Medical Sciences, 2021)
Background and Aims: The need to use a highly effective sealer in order to create a complete seal along the canal is essential for the basic treatment of tooth roots. Therefore, the aim of this study was to investigate the sealing ability of cold ceramic and gutta-percha with sealer by applying the bacterial leakage and electrochemical method. Materials and Methods: In this in-vitro experimental study, fifty human single-rooted teeth were selected and their crowns were cut from the cervical region. The canals were prepared and washed with 17% EDTA. Then the teeth were randomly divided into four groups: group 1 gutta-percha with AH26 sealer (Dentsply Detrey, Germany) (n=20), group 2 cold ceramic (Yazd, Iran) (n=20), negative and positive control groups which each consisted of 5 teeth. Samples were kept in an incubator at 37° C for 48 hrs. Two coats of nail polish were used for covering the root, except for the last 2 mm, and microleakage in the fillings was measured by the bacterial leakage and electrochemical methods. The microleakage of the two groups was statistically analyzed in the electrochemical technique by Student's t-test, and in the bacterial leakage method by Fisher's exact test. Results: In bacterial leakage method, in the first group (gutta-percha) 7 samples (35%) and in the second group (cold ceramic) 3 samples (15%) had bacterial leakage, but no significant difference was observed between the two groups on different days (P>0.05). The mean microleakage based on the electrochemical technique in gutta-percha was significantly higher than that of cold ceramic (P=0.0001). Conclusion: According to the lower microleakage values in the use of cold ceramic compared to gutta-percha, cold ceramic  can be used to fill root canals to reduce microleakage, although further studies are needed.